Innovative gamification and outreach tools to raise awareness about antimicrobial resistance - Tarín-Pelló, Antonio; Marco-Crespo, Elisa; Suay-García, Beatriz; Galiana-Roselló, Carolina; Bueso-Bordils, José I.; Pérez-Gracia, María-Teresa (Frontiers in Microbiology, 2022)
Since 2017, the SWICEU team has developed various informative actions and innovative gamification supports to educate and raise awareness about antimicrobial resistance (AMR) and the correct use of antibiotics among the general population and, especially, among young people. This case study presents the results obtained in the last five years with the strategies carried out by this team, composed of students and professors of Health Sciences, Industrial Design Engineering and Communication Sciences at CEU Cardenal Herrera University (CEU UCH) in Valencia (Spain). Over the past five years, playful educational supports have been developed to make the health problem of bacterial resistance and the action of antibiotics more understandable among young people. The decks of cards, cluedo and escape room type games designed have obtained funding from the Spanish Foundation for Science and Technology (FECYT) of the Spanish Ministry of Science and Innovation. The dissemination media used, with the same objective of teaching and raising awareness about AMR in a creative and innovative way, have been selected according to the trends in digital communication and use of scientific and health content provided by the most recent studies carried out among the Spanish population. These strategies have included decalogues or 'tips' with useful advice, infographics, YouTube videos, Twitter threads, online challenges on Kahoot, stories on Instagram, use of QR codes, etc. These actions have also obtained diffusion in the media and have been awarded by different national and international entities. The good results obtained in the case under study allow us to establish recommendations for the design of innovative educational gamification and dissemination supports on AMR, especially aimed at younger audiences.